Indonesia Sistem Informasi E-Kondektur Untuk Transaksi Tiket Bus - Mochamad Subianto; Rendy Jhon Kailola; Paulus Lucky Tirma Irawan; Oesman Hendra Kelana (LPPM STIKI MALANG, 2023)
Cconventional or paper ticket sales still have a higher percentage of sales. It is because passengers being able to directly meet with a travel agent and obtain information more easily, as well as avoiding errors in the destination listed on the ticket because the purchase is made directly. However, the security and efficiency of the paper ticket model can still be improved. Another problem are they lack information about the bus arrival time, the seating capacity on the bus (full or not), and the bus route. On the other hand, buses that have already started their journey must transport passengers at bus stops along the route if the bus seats have not yet been filled. This research will develop a new bus ticket payment system model using a smartphone medium called Ticket on the Road. This model will replace the paper ticket model carried by the bus conductor. By using a smartphone and a small printer, the bus conductor can print a complete payment receipt with the actual fare. This model is expected to increase transaction security and efficiency while reducing ticket printing costs.